Sound and Sentiment : Birds, Weeping, Poetics, and Song in Kaluli Expression, 3rd edition with a new introduction by the author - Feld, Steven (Book collections on Project MUSE., 2012)
"This thirtieth anniversary edition of Sound and Sentiment makes Steven Feld's landmark, field-defining book available to a new generation of scholars and students. A sensory ethnography set in the rain forest of Papua New Guinea, among the Kaluli people of Bosavi, Sound and Sentiment introduced the anthropology of sound, or the cultural study of sound. After it was first published in 1982, a second edition, incorporating additional field research and a new postscript, was released in 1990. The third edition includes all of the material from the first two editions, along with a substantial new introduction in which Feld discusses Bosavi's recent history and reflects on the challenges it poses for contemporary theory and representation."--Publisher's description